Molecular quadrupole moments promote ground-state charge generation in doped organic semiconductors - Privitera, A; Londi, G; Riede, M; D'Avino, G; Beljonne, D (Wiley, 2020)
The role of local environmental interactions on the generation of free charge carriers in doped organic layers is investigated. Via a classical micro‐electrostatic model, a dual effect of molecular quadrupole moments of host and dopant molecules on doping is demonstrated. Namely, electrostatic interactions ease ionization of the dopant by altering the energy level alignment between the host and the dopant and reduce the barrier for charge dissociation by flattening the energy landscape around the ionized dopants. These results indicate that tailoring molecular quadrupole moments of the host and/or dopant are an attractive strategy toward improved doping efficiency in organic semiconductors.